2009
DOI: 10.1021/ic9021728
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structures, and Multinuclear NMR Spectra of Tin(II) and Lead(II) Complexes of Tellurium-Containing Imidodiphosphinate Ligands: Preparation of Two Morphologies of Phase-Pure PbTe from a Single-Source Precursor

Abstract: Group 14 metal complexes of heavy chalcogen-centered anions, M[(TeP(i)Pr(2))(2)N](2) (5, M = Sn; 6, M = Pb) and M(TeP(i)Pr(2)NP(i)Pr(2)Se)(2) (7, M = Sn; 8, M = Pb), were synthesized in 64-89% yields by metathesis of alkali-metal salts of the ligands with group 14 metal dihalides. Crystallographic characterization of the complexes revealed that 5, 6, and 8 engage in metal...chalcogen secondary bonds to generate dimers, whereas 7 is monomeric in the solid state. Multinuclear ((1)H, (31)P, (77)Se, and (125)Te) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 38 publications
4
36
0
Order By: Relevance
“…XRD is deemed to be one of the most useful techniques for obtaining structural microcrystalline information regarding the studied compounds . Also, it is usually applied to provide an explicit view concerning the lattice dynamics of compounds in the solid phase . Hence, the XRD patterns of the ligand (H 2 L) and complexes 1 – 5 were obtained in the 0° < 2 θ < 90° range of scattering angle.…”
Section: Resultsmentioning
confidence: 99%
“…XRD is deemed to be one of the most useful techniques for obtaining structural microcrystalline information regarding the studied compounds . Also, it is usually applied to provide an explicit view concerning the lattice dynamics of compounds in the solid phase . Hence, the XRD patterns of the ligand (H 2 L) and complexes 1 – 5 were obtained in the 0° < 2 θ < 90° range of scattering angle.…”
Section: Resultsmentioning
confidence: 99%
“…106,107 The PbSe films were grown at 250-500 1C and powder XRD showed that the cubic form of PbSe had formed at all temperatures. 106,107 The PbSe films were grown at 250-500 1C and powder XRD showed that the cubic form of PbSe had formed at all temperatures.…”
Section: Groups 14 and 16 (Iv-vi) Thin Filmsmentioning
confidence: 99%
“…We have reported the use of [bis(diselenoimidodialkylphosphinato)lead(II)] [Pb{N(PR 2 Se) 2 2 ] complexes as singlesource precursors for the deposition of PbSe thin films by low-pressure LP-CVD and aerosol-assisted (AACVD) experiments. [59][60][61][62] However, the deposited films have signifi- cant levels of phosphorus contamination with the phosphorus originating from the precursor. [59] Recently, it was shown that cadmium complexes of N,N-dialkyl-NЈ-acylthiourea or the corresponding N,N-dialkyl-NЈ-acylselenourea can be used as single-source precursors for the synthesis of CdS or CdSe nanoparticles.…”
Section: Introductionmentioning
confidence: 99%